Analysis of Academic Performance and Geographic Disparities in Virtual University’s B. Ed Early Childhood Education Program - Ahmed, Munawwar; Malik, Farheen; Riaz, Meimoona (JECCE, 2025)
The research examined the scholastic achievement and geographical gap among the students of the B.Ed. (Hons) Early Childhood Care and Education (ECCE) program in Virtual University of Pakistan. The research questions were: (1) to assess the general academic performance and credit completion, (2) to check the correlation between Cumulative Grade Point Average (CGPA) and courses failed, (3) to find differences in performance along geographic lines. The research design used was a quantitative non-experimental one based on the secondary academic information at the university Virtual Information System (VIS). The sample of the study was all the 83 students pursuing a particular cohort, and they were classified into five regions namely Punjab Metros, Sindh Metros, Small Towns, ICT (Islamabad Capital Territory), and Overseas. The analysis of data was performed with the help of descriptive statistics, Pearson correlation, and one-way ANOVA. The findings showed that, there was a significant negative correlation between CGPA and the failed courses (r = -.923, p <.001). One-way ANOVA showed that there were statistically significant differences in the mean CGPA by regions, F(4, 78) = 4.39, p =.003, with students in Punjab Metros doing the best and those in ICT doing the worst. Its results emphasize the essential role of the course failure on the overall achievement and the ongoing geographic disparities in outcomes of online learning. The paper suggests that at-risk students should receive specific academic interventions and policies be implemented to deal with the infrastructural and support-service differences across regions in order to facilitate educational equity in virtual teacher education.